2015
DOI: 10.1016/j.physa.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Coherent measures of the impact of co-authors in peer review journals and in proceedings publications

Abstract: This paper focuses on the coauthor effect in different types of publications, usually not equally respected in measuring research impact. A priori unexpected relationships are found between the total coauthor core value, ma, of a leading investigator (LI), and the related values for their publications in either peer review journals (j) or in proceedings (p). A surprisingly linear relationship is found: m arXiv:1506.05375v1 [physics.soc-ph] 17 Jun 2015 the findings suggest an immediate test of coherence of scie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is, of course, nothing wrong in citing an editor (of a special issue or proceedings of a conference) for his/her particular achievement, in particular in papers published through such means. In fact, it has been shown that there is some fair balance between co-authorship and scientific recognition indices for classical peer review papers and "special issues" (in a broad sense, i.e., including proceedings outside of journals) [29][30][31]. Thus, it is good for the scientific peer review process that new editors appear on editorial boards, especially when an individual has demonstrated editorial skill.…”
Section: Introductionmentioning
confidence: 99%
“…There is, of course, nothing wrong in citing an editor (of a special issue or proceedings of a conference) for his/her particular achievement, in particular in papers published through such means. In fact, it has been shown that there is some fair balance between co-authorship and scientific recognition indices for classical peer review papers and "special issues" (in a broad sense, i.e., including proceedings outside of journals) [29][30][31]. Thus, it is good for the scientific peer review process that new editors appear on editorial boards, especially when an individual has demonstrated editorial skill.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of the rank-size theory for applications mirrors in the popularity of such a framework in different fields, ranging from metrics of science and bibliometrics (see, e.g., Ausloos, 2013Ausloos, , 2015Chatterjee et al, 2016;Mansilla et al, 2007) to seismology (see, e.g., Ficcadenti and Cerqueti, 2017), text analysis and linguistics (see, e.g., Ficcadenti et al, 2019Ficcadenti et al, , 2020Montemurro, 2001) and, of course, economics (see, e.g., Brakman et al, 1999;Cerqueti and Ausloos, 2015;Córdoba, 2008;Dimitrova and Ausloos, 2015;Giesen and Südekum, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, in addition to teaching and education, scientific research and performance is one of the main concerns of an elite university. Universities compete on the basis of their scientific production against each other to attract competitive research funding and student finance from the Government to enable them to support progress and competitiveness (Altbach 2009, Andrei et al 2016, Ausloos 2015, Bibu et al 2016, Florescu 2012, Popa et al 2019.…”
Section: Introductionmentioning
confidence: 99%